A hittite scribal tradition predating the tablet collections of Ḫattuša? - Kloekhorst, Alwin (Zeitschrift für Assyriologie und vorderasiatische Archäologie, 2019)
This article discusses the origins of a group of four Hittite OS tablets, which share some unique and peculiar features with respect to their shape, spelling conventions and palaeography. It argues that these four tablets are the oldest documents of the Hittite corpus, and that they were not created in Ḫattuša, but have been imported from elsewhere. Originally, they belonged to an older writing tradition, predating the establishment of Ḫattuša as the Hittite capital. This implies that the royal tablet collections in Ḫattuša do not reflect the very first beginnings of Hittite cuneiform, but only the start of a royal administration there. The typical Hittite ductus was already created in the 18th century BCE – in Kuššara, Nēša or elsewhere in Anatolia.